Influence of calcium hydroxide residues after using different irrigants on the accuracy of two electronic apex locators: An in vitro study - Nooshin Sadat Shojaee; Zahra Zaeri; Mohammad Mehdi Shokouhi; Fereshteh Sobhnamayan; Alireza Adl (Wolters Kluwer Medknow Publications, 2020)
Background: The purpose of this study was to evaluate the effect of calcium hydroxide (Ca[OH]2)residues on the accuracy of two electronic apex locators (EALs) (Root ZX and Raypex 6) in the presence of different irrigants. Materials and Methods: In this an in vitro study Eighty single-rooted human mandibular premolars were selected. The crowns of the teeth were removed to standardize the working lengths (WLs). Actual WLs (AWLs) were recorded, and the root canals were shaped using protaper rotary instruments up to size F3. Then, the root canals were dried and filled with injectable Ca (OH)2paste and the access cavities were temporarily sealed. Teeth were put into four alginate boxes, including two experimental groups (n = 30) and two control groups (n = 10). The pools of alginate were wrapped in wet gazes and stored at 37°C and 100% humidity for 7 days. Then, the root canals were exposed and Ca (OH)2paste was removed by normal saline or 5.25% sodium hypochlorite irrigation followed by 17% ethylenediaminetetraacetic acid (EDTA), and the electronic WL (EWL) was measured by Root ZX and Raypex 6. Differences of EWL from AWL were calculated. Furthermore, the percentage of acceptable measurements (tolerance limit of ± 0.5 and ± 1 mm) was calculated for each apex locator. One-way ANOVA test with post hoc paired t-test and Chi-square test was used to analyze the data (P < 0.05). Results: The results showed that there was no significant difference between the accuracy of two EALs and irrigants (P > 0.05). Conclusion: The present study revealed that no statistically significant differences were observed between the two apex locators after Ca(OH)2paste removal with different irrigants.